TGF-β activation by bone marrow-derived thrombospondin-1 causes Schistosoma- and hypoxia-induced pulmonary hypertension - Rahul Kumar (Nature Portfolio, 2017)
Thrombospondin-1 (TSP-1) activates latent TGF-β in the extracellular matrix. Here the authors show that inappropriate activation of latent TGF-β in murine, bovine and human lung by monocyte-produced TSP-1 causes pulmonary hypertension, and that interference with the activation process prevents disease development.